1997
DOI: 10.1103/physrevb.55.13822
|View full text |Cite
|
Sign up to set email alerts
|

Surface structure of cadmium selenide nanocrystallites

Abstract: Extended x-ray-absorption fine structure ͑EXAFS͒, Fourier-transform infrared absorption ͑FTIR͒, and elemental analysis were used on a variety of CdSe nanocrystallites ͑NC's͒ to study surface structure. All CdSe NC's were grown by standard inverse micelle techniques. Two sets of NC's samples were made. One set was made so that only the size of the NC's was varied, while the surface treatment was kept the same. The other set was made so that only the surface treatment was varied, while the size distribution was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
62
2

Year Published

2000
2000
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(69 citation statements)
references
References 28 publications
(23 reference statements)
5
62
2
Order By: Relevance
“…These sites are capable of trapping electrons or holes at the surface. Ab initio calculations (27) and positron annihilation spectroscopy on CdSe NCs (24) suggest that Se atoms relax outward irrespective of passivation, indicating, as previously suggested (25,(28)(29)(30), that hole traps constitute the majority surface trap site. The precise number of trap sites around a NC is likely to be both inhomogeneous and sample dependent; although consideration of the number of atoms near the surface in a wurtzite NC puts an approximate upper limit on that number (25).…”
mentioning
confidence: 74%
“…These sites are capable of trapping electrons or holes at the surface. Ab initio calculations (27) and positron annihilation spectroscopy on CdSe NCs (24) suggest that Se atoms relax outward irrespective of passivation, indicating, as previously suggested (25,(28)(29)(30), that hole traps constitute the majority surface trap site. The precise number of trap sites around a NC is likely to be both inhomogeneous and sample dependent; although consideration of the number of atoms near the surface in a wurtzite NC puts an approximate upper limit on that number (25).…”
mentioning
confidence: 74%
“…According to previous experimental [30,31,32,33,34] and theoretical [14] work, group VI elements (such as S and O) bond preferentially to the Cd atom surface sites on the nanocrystal. Consequently, this calculation is made for each of the sp 3 s * Cd basis orbitals on the 84 surface Cd sites of the 3.4 nm diameter nanocrystal, and for each of the sp 3 s * Cd basis orbitals on the 243 surface Cd sites of the 5.0 nm diameter nanocrystal, over energy intervals of ∆E = 0.01 eV.…”
Section: Theory a Semiempirical Hamiltonian Calculationmentioning
confidence: 99%
“…A many-shell PDF analysis of nanocrystalline diamond showed no simple relationship between the distance shifts of the first 8 shells (most shells showed contraction, but one showed expansion) [18]. Similarly, Carter et al report a first shell contraction and a second shell expansion from EXAFS analysis of CdSe [11]. In general, small particle size and the presence of bond-bending disorder prevents meaningful structure analysis of second and higher shells in EXAFS data from nanoparticles.…”
Section: B Exafs Analysismentioning
confidence: 99%
“…Studies on tetrahedrally-coordinated semiconductor nanoparticles have found that the first shell bond length may be modified [9,10,11] or unchanged [12,13,14] with respect to the bulk material. Rockenburger et al concluded that the nature of the surface ligand determined the direction of bond length changes [9].…”
Section: B Exafs Analysismentioning
confidence: 99%
See 1 more Smart Citation